Minimal change disease following COVID-19 vaccination: A systematic review - Kechagias, Konstantinos S.; Laleye, Joshua D.; Drmota, Jan; Geropoulos, Georgios; Kyrtsonis, Georgios; Zafeiri, Marina; Triantafyllidis, Konstantinos Katsikas; Stathi, Dimitra (PLOS ONE, 2024)
Background The newly developed COVID-19 vaccines are highly effective and safe. However, a small portion of vaccine recipients experience a wide range of adverse events. Recently, glomerular disease, including the development of Minimal Change Disease (MCD), has been observed after administration of different COVID-19 vaccines, although causality remains a matter of debate. Aim The aim of this systematic review was to comprehensively examine the available literature and provide an overview of reported cases of MCD following vaccination against SARS-CoV-2. Results We identified 46 eligible articles which included 94 cases with MCD following COVID-19 vaccination of which one case was reported twice due to a second relapse. Fifty-five participants were males (59.1%, 55/93) and 38 (40.9%, 38/93) were females with a mean age of 45.02 years (SD:20.95). From the included patients 50 (50/94, 53.1%) were described as new-onset and 44 (46.9%, 44/94) as relapse. On average, symptomatology developed 16.68 days (SD: 22.85) after the administration of the vaccine irrespective of the dose. Data about symptoms was reported in 68 cases with the most common being oedema (80.8%, 55/68), followed by weight gain (26.5%, 18/68) and hypertension (16.1%, 11/68). In terms of outcome, more than half of the patients went into remission (61%, 57/94), while 18 recovered or improved post treatment (19.1%, 18/94). Two people relapsed after treatment (2.1%, 2/94) and two cases (2.1%, 2/94) were reported as not recovered. Conclusion MCD is possibly a condition clinicians may see in patients receiving COVID-19 vaccines. Although this adverse event is uncommon, considering the limited published data and the absence of confirmed causality, increased clinical awareness is crucial for the early recognition and optimal management of these patients.